Ibrutinib monotherapy outside of clinical trial setting in Waldenström macroglobulinaemia: practice patterns, toxicities and outcomes. (29th August 2019) - Abeykoon, Jithma P.; Zanwar, Saurabh; Ansell, Stephen M.; Gertz, Morie A.; Kumar, Shaji; Manske, Michelle; Novak, Anne J.; King, Rebecca; Greipp, Patricia; Go, Ronald; Inwards, David; Muchtar, Eli; et al.
Summary: Ibrutinib‐related data in Waldenström macroglobulinaemia (WM) remain sparse, particularly outside of trials. We report on 80 patients [previously treated, n  = 67 (84%), treatment‐naïve, n  = 13 (16%)] with WM, evaluated consecutively at Mayo Clinic, who received ibrutinib off‐study after its approval in 2015 for WM. Overall response rate (ORR) was 91%; major‐response rate (MRR) was 78%. The median time to first response and best response was 2·9 [95% confidence interval (CI): 2–4] and 5·7 (95% CI: 4–12) months, respectively. The median follow‐up was 19 (95% CI: 14–21) months; 18‐month progression‐free survival (PFS) was 82%. The median time on therapy was 12·5 (95% CI: 9·3–16·7) months, and the median duration‐of‐response was 32 (range: 23–32) months. Twenty‐five patients (31%) had discontinued therapy at last follow‐up (68% due to treatment‐related toxicities) and 18% of patients required dose reduction. Fatigue (12%) and atrial‐fibrillation (11%) were common non‐haematological toxicities. IgM rebound occurred in 36% of patients who abruptly discontinued ibrutinib. Following ibrutinib discontinuation, 84% of patients received subsequent treatment, achieving an ORR of 57% and MRR of 50%. The median PFS from commencement of subsequent salvage therapy was 18 months. Ibrutinib therapy, outside of clinical trials, is effective in WM, but is associated with toxicities and challenges, including IgM rebound and a high drug discontinuation rate for reasons other than disease progression.